The impact of experiential learning on managers' strategic competencies and decision style - Pedro M. Torres; Mário Gomes Augusto (Journal of Innovation & Knowledge (JIK), 2017)
This research studies whether Executive MBA student's participation in a business strategy simulation course significantly impacts on self-perceptions of their strategic competencies and decision style, which involves crossing psychological and strategy fields, and aims to contribute to the development of theoretical management and educational insights. The obtained results on students' self-perception of their improvement on strategic competencies suggest that the simulation has a positive value for students and contributes both to their engagement in the MBA program and to their knowledge. However, decision-making styles do not change as a result of the simulation, with the exception of the analytical component, which is reinforced. Thus, we concluded that although students' knowledge and strategic competencies could be expanded with a business strategy simulation, their decision-making style is not significantly influenced by practice. Consequently, we suggest that it is possible to antecipate one reaction to a future situation, when managers' decision-making style is known in advance, which in turn validates the statement that "nothing is so theoretical as good practice".
Keywords: A23; M10; 650; Decision-making styles; Strategic competencies; Experiential learning; Simulation-based method